Diallyl disulphide inhibits apolipoprotein(a) expression in HepG2 cells through the MEK1-ERK1/2-ELK-1 pathway. Issue 1 (December 2017) - Ma, Xiaofeng; Liu, Yami; Tan, Yanmei; Qu, Kai; He, Xinglan; Zhang, Hai; Wang, Zuo
Abstract Background Lipoprotein(a) [LP(a)] is implicated as a common and independent risk factor for cardiovascular diseases. The therapeutic options currently available for reducing plasma LP(a) concentrations are limited. Diallyl disulphide (DADS), the main component of garlic, regulates lipid metabolism in hepatocytes and adipocytes through ERK1/2 signalling. This study aimed to assess the effect of DADS on apolipoprotein(a) [apo(a)] in HepG2 cells. We also determined the effects of DADS on apo(a) expression and secretion in HepG2 cells as well as the underlying mechanisms. Methods We examined the role of DADS on apo(a) expression in HepG2 cells by treating cell with different concentrations of DADS (10, 20, 40 and 80 μg/mL) for 24 h or treating cells with 40 μg/mL DADS for 0, 6, 12, 24 and 48 h. Then we used quantitative real-time PCR to analysis apo(a) mRNA levels, used Western blot to analysis apo(a) protein levels and used enzyme-linked immunosorbent assay to test apo(a) secreted levels. To farther determined the role of DADS, we applied Transfection of small interfering RNA to knockdown ELK-1levels and applied PD98059, a specific inhibitor of ERK1/2, to block ERK1/2 signal. Results The results show DADS inhibited apo(a) at both the mRNA and protein levels in HepG2 cells in a dose-dependent manner. DADS-mediated inhibition of apoa(a) expression in HepG2 cells was attenuated when the cells were cultured in medium containing PD98059 (ERK1/2 inhibitor) or were transfected with siRNAs against MEK1 or ELK-1. Overexpression of apo(a) yielded similar results. Conclusions This study reveals that DADS can downregulate apo(a) expression in a dose-dependent manner via the MEK-ERK12-ELK-1 pathway.